Duration of first vaginal birth following cesarean: Is stage of labor at previous cesarean a factor?. (September 2020) - Rottenstreich, Misgav; Futeran Shahar, Chen; Rotem, Reut; Sela, Hen Y.; Rottenstreich, Amihai; Samueloff, Arnon; Shen, Ori; Reichman, Orna
Abstract: Objective: Parturients in second delivery undergoing vaginal birth after cesarean (VBAC) are divided to those who had their cesarean delivery (CD) while in labor as opposed to those who had an elective CD. We aimed to study if the stage of labor that was present during the primary CD is associated with the duration of subsequent spontaneous VBAC. Methods: A retrospective study (2006–2014). Multiparas in second delivery with a history of a CD (P2-VBAC) were sub-grouped based on stage of labor at which the CD was performed in the first delivery; elective, latent, first or second stage of labor, Duration of labor was compared between P2-VBAC (as one group and further as the sub-groups) to primiparas (P1), multiparas in second (P2) and third (P3) vaginal delivery (VD). A Cox regression analysis was performed including maternal age, preterm-delivery, regional anesthesia, oxytocin augmentation, birthweight and neonatal gender. Results: A total of 58, 028 parturients were included in the study. Mean duration of labor was significantly longer in parturients with a first VD (P1 and P2-VBAC) compared to repeat VD (P2 and P3), 6.0 versus 2.5 h, respectively, ( P  < 0.001). Analyzing duration of labor by the sub-groups of P2-VBAC revealed that spontaneous VD following a second-stage CD was associated with shorter duration of labor when compared with spontaneous VD following elective, latent and active first stage CD 4.2 versus 6.3, 7.0, 6.9 h respectively, p<0.001. Conclusion: Second stage CD shortens duration of the following VBAC compared to those who underwent cesarean in earlier stages of labor.